Uma proposta de correção semiautomática de questões discursivas e de visualização de atividades para apoio à atuação do docente - Pissinati, Eduardo Marim (2014)
The task of correcting discursive texts requires much effort and dedication from teachers. The larger the number of students, the bigger the work is, until it reaches a point where the teacher fails to apply these activities since he cannot evaluate them, subjecting his students only to objective questions. Furthermore, the identification of students who need more attention is impaired in very large groups. Increasing the number of teachers per class could solve these problems, but more teachers represent more costs to the institution. In this context, the use of the computer can assist in these activities without including new teachers. However this strategy must be well thought not to overload the teacher with inadequate tools. This paper presents a tool for semi-automatic correction of discursive texts and a visualization tool that will allow the teacher to monitor individual performances of their students even in large classes. The semi-automatic correction tool uses intelligent recovering techniques of the information as clustering to correct discursive answers. Besides that, the visualization tool uses information visualization techniques to present the results to the teacher. Both were integrated with Moodle Virtual Learning Environment in order not to change the normal routine of work of those who use it.